GATA-4 and Nkx-2.5 Coactivate Nkx-2 DNA Binding Targets: Role for Regulating Early Cardiac Gene Expression - Sepulveda, Jorge L. (American Society for Microbiology, 1998)
The cardiogenic homeodomain factor Nkx-2.5 and serum response factor (SRF) provide strong transcriptional coactivation of the cardiac α-actin (αCA) promoter in fibroblasts (C. Y. Chen and R. J. Schwartz, Mol. Cell. Biol. 16:6372–6384, 1996). We demonstrate here that Nkx-2.5 also cooperates with GATA-4, a dual C-4 zinc finger transcription factor expressed in early cardiac progenitor cells, to activate the αCA promoter and a minimal promoter, containing only multimerized Nkx-2.5 DNA binding sites (NKEs), in heterologous CV-1 fibroblasts. Transcriptional activity requires the N-terminal activation domain of Nkx-2.5 and Nkx-2.5 binding activity through its homeodomain but does not require GATA-4’s activation domain. The minimal interactive regions were mapped to the homeodomain of Nkx-2.5 and the second zinc finger of GATA-4. Removal of Nkx-2.5’s C-terminal inhibitory domain stimulated robust transcriptional activity, comparable to the effects of GATA-4 on wild-type Nkx-2.5, which in part facilitated Nkx-2.5 DNA binding activity. We postulate the following simple model: GATA-4 induces a conformational change in Nkx-2.5 that displaces the C-terminal inhibitory domain, thus eliciting transcriptional activation of promoters containing Nkx-2.5 DNA binding targets. Therefore, αCa promoter activity appears to be regulated through the combinatorial interactions of at least three cardiac tissue-enriched transcription factors, Nkx-2.5, GATA-4, and SRF.